New possibilities of nephroprotection in patients with chronic heart failure in combination with chronic kidney disease and diabetes mellitus 2 or without it - E. V. Kovalenko; L. I. Markova; O. L. Belaya (Лечащий Врач)
Impaired kidney function has a negative impact on the course of heart failure in both patients with and without diabetes mellitus. Therefore, the development and study of the effectiveness of methods for the treatment of chronic heart failure, especially in patients with diabetes mellitus and chronic kidney disease, in order to improve the prognosis and reduce the risk of cardiorenal complications, is a priority for modern medicine. Inhibitors of the sodium glucose co-transporter type 2 today have a strong evidence base, not only as hypoglycemic drugs. Representatives from this group demonstrated cardiovascular safety and high efficacy in patients with chronic heart failure, both with reduced (EMPEROR reduced, DAPA-HF studies) and preserved left ventricular ejection fraction (EMPEROR-Preserved, DELIVER studies), regardless of the presence of sugar diabetes. An additional analysis of the conducted studies and specially planned projects showed the nephroprotective properties of the drugs. Long-term use of inhibitors of the sodium glucose co-transporter type 2 reduced the risk of progression of renal failure to the end stage and the severity of albuminuria in patients with chronic kidney disease. The proven cardiorenoprotective effects of gliflozins have expanded the boundaries of their clinical application. However, not all representatives of this group registered in our country can be recommended for patients with chronic heart failure and chronic kidney disease. From the standpoint of evidence-based medicine, dapagliflozin, empagliflozin, and canagliflozin have indications for use in various clinical situations. The article presents the results of randomized clinical trials on the use of sodium-glucose co-transporter type 2 inhibitors in patients with cardiovascular diseases, chronic heart failure, chronic kidney disease with and without type 2 diabetes mellitus. The effect of gliflozins on the course of chronic heart failure and renal outcomes was analyzed. The data of the latest studies CREDENCE, Dapa-CKD, EMPEROR-Preserved, VERTIS CV, STELLA-LONG TERM are covered in more detail. Keywords: chronic heart failure, chronic kidney disease, diabetes mellitus, type 2 sodium-glucose co-transporter inhibitor, empagliflozin, dapagliflozin, kanagliflozin, ertugliflozin, ipragliflozin.